Hands-on transfer learning with Python : implement advanced deep learning and neural network models using tensorflow and keras /: implement advanced deep learning and neural network models using tensorflow and keras. (2018) - Sarkar, Dipanjan; Bali, Raghav; Ghosh, Tamoghna
No abstract available